ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRES KERJA ANGGOTA POLISI DI KEPOLISIAN SEKTOR WILAYAH KABUPATEN TIMOR TENGAH SELATAN - Nincia Y Manu; Erni Raster Klau; Fredericksen Amseke (Institut Agama Kristen Negeri Manado, 2022)
Abstract This study aims to find out what factors influence the work stress of police members in the TTS Regency Regional Police Department. This research is a regression analysis research with a quantitative approach. The research sampling obtained using a total sampling technique involving 64 members of the yaggi Police in the Niki-niki, Batu Putih, South Mollo, and North Mollo,District of South Central Timor.This type of research is an experiment using the results of the T test show the variables of work factors have a positive and significant effect on work stress, while the factors outside of work have a positive but not significant effect. Furthermore, the aspects of the work factors that have the most influence on work stress are aspects of individual routine work factors because the significant value is 0.001<0.005 and R square is 17%. The aspects of work factors that have the lowest influence on job stress are aspects of opportunity participation because the significance value is 0.147>0.05, and R square 0.8%. while the aspects of the variables outside the work that have most influence on work stress are aspects of life structure improvement because the significant value is 0.103>0.05 and R square is 4.2%. and the aspects of the lowest influence were the flexibility or rigid aspects, obtainted a significant value of 0.925>0.5.